From "solitary thinkers" to "social actors": OER in multilingual CALL teacher education - Shona Whyte (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Among many dilemmas in educational practices in today's networked environments is the question of language teacher preparation for tomorrow's world. Secondary school teachers of modern foreign languages face multiple challenges in making the transition from the relatively closed scholastic tradition of university ivory towers, which are often resistant to digital cultures, to classroom contexts with different expectations regarding the technological mediation of teaching and learning. Open educational resources (OER) have an important role to play in this transition, as do open education practices (OEP). The present paper examines a hybrid computer-assisted language learning (CALL) course for pre-service teachers at a French university as a context for developing OER awareness. Trainee teachers of different foreign languages completed individual and collective tasks using blogs, wikis and social media to a) share examples of teaching and learning activities, b) research and filter web-based teaching resources, and c) discuss technology use for language teaching. The study investigates the design of teaching activities and motivations for creating, identifying and sharing OER, identifying areas of concern for these teachers and highlighting contrasting views of both language teaching and professional development. The paper thus sheds light on both the process and the products of this form of CALL teacher education, and concludes with implications regarding the changing social roles of both language learners and their teachers in relation to the goals of the OER/OEP movement.